Metacognitive Strategies and Test Performance: An Experience Sampling Analysis of Students' Learning Behavior. (1st November 2012) - Nett, Ulrike E.; Goetz, Thomas; Hall, Nathan C.; Frenzel, Anne C.
Abstract : The aim of the present study was to explore students' learning-related cognitions prior to an in-class achievement test, with a focus on metacognitive strategy use. A sample of 70 students in grade 11 (58.6% female, M age = 17.09 years) completed a series of structured, state-based measures over a two-week period via the experience sampling method until the day before a class test. Results illustrated students' self-regulatory ability to preserve their motivational and cognitive resources, with test-related cognitions evidenced significantly more often in learning-related as opposed leisure settings. Metacognitive strategy use was also found to significantly increase as the test date approached underscoring the goal-oriented nature of situated learning behaviors. Higher intercepts and increases in frequency of test-related cognitions over time positively corresponded to test performance. Of the three metacognitive strategies assessed, monitoring was found to positively correspond with test performance. Implications for future practice as well as implications for future research employing the experience sampling method are discussed.